Protective effect of S-adenosylmethionine against galactosamine-induced injury of rat hepatocytes in primary culture - Kučera, Otto; Červinková, Zuzana; Lotková, Halka; Křiváková, Pavla; Roušar, Tomáš; Mužáková, Vladimíra; Héžová, Renata; Kanďár, Roman; Rudolf, Emil (Physiological research, 2006)
The protective effect of S-adenosylmethionine (SAMe) on D-galactosamine (GalN)-induced damage to rat hepatocytes was tested in primary cultures. SAMe at concentrations of 50 and 1000 mg/l significantly reduced lactate dehydrogenase release from cells injured by 40 mM GalN after 24 h of incubation. There were no significant changes in urea production after 24 h among tested groups, including control hepatocytes. Exposure of hepatocytes to GalN leads to 3.5-fold decrease in urea synthesis after 48 h in comparison with control cell cultures. Addition of the highest dose of SAMe (1000 mg/l) into the culture media attenuated this decrease by 180 %. None of the tested doses of SAMe (5, 25, 50 and 1000 mg/l) affected considerably the reduced activity of mitochondrial dehydrogenases. The content of reduced and oxidized glutathione in GalN-exposed cells was diminished to 1.5 % and 16 %, respectively, of the control values after 24 h. Using only the highest concentration SAMe increased significantly these contents. SAMe had no effect on dramatically decreased albumin synthesis. These findings indicate beneficial effect of SAMe, especially of the highest concentration, on GalN-induced toxicity to rat hepatocytes in primary culture. This action of SAMe seems to be associated with reduction of plasma membrane damage and increased synthesis of glutathione.
Keywords: potkani Wistar; Galactosamine; glutathion; S-Adenosylmethionine; Microscopy, Fluorescence; In Vitro Techniques; fluorescenční mikroskopie; Hepatocytes; techniky in vitro; Rats, Wistar; hepatocyty; Glutathione; galaktosamin; Financing, Government; S-adenosylmethionin; financování vládou